The development of e-rating book system for web OPAC in PTAR 4 Universiti Teknologi MARA / Noradiela Ezza Shuib - Shuib, Noradiela Ezza (Faculty of Computer and Mathematical Sciences, 2006)
This project is to develop a rating book system in PTAR4 library. This project focused on the rating and feedback that given by the reader. The main purpose of this project is to solve the current problem that happens to the reader during reservation such as they spent time for choosing the suitable book because the reader doesa^t know the quality of the book. Through this project, reader can view the feedback fiom previous reader and view the rating of the book. Besides that, reader can add new feedb£K:k and make rating to any book. This book will be categorized by using genre. From this feedback and book rating, reader will get some information to guide them in making decision.